Pemberdayaan Kelompok Wanita Tani “Sri Rejeki” Melalui Budidaya Tanaman Sayuran di Bantul, DIY - Ismiasih Ismiasih; Resna Trimerani; Christina Wahyu Ary Dewi; Helmi Afroda (Politeknik Negeri Cilacap, 2023)
Women have an important role in a family. In supporting their role, many women are active in community organizations, one of which is the Women Farmers Group (KWT). However, KWT is often used only for meeting women without any productive activities. Therefore, through this community service program (PKM), it is hoped that it can raise independence for mothers to have productive. The partner in this PKM activity is KWT